Preliminary study of the efficiency of alkaline water electrolysis for hydrogen production using an ultrasonic electrode (Research, Society and Development, 2024)
This study presents research on increasing the efficiency of alkaline water electrolysis for green hydrogen production using ultrasonic electrodes. The aim of the work was to investigate the efficiency of alkaline water electrolysis using ultrasonic electrodes, focusing on green hydrogen production and environmental sustainability. The methodology involved the use of a stainless steel electrolytic cell, 316L stainless steel electrodes, and a 30% (w/w) KOH electrolyte solution. A 20W, 40kHz ultrasonic generator was used, applying ultrasound directly to the electrode. The hydrogen produced was collected through a water displacement system. The experimental design followed a full factorial design, with data analysis by analysis of variance (ANOVA) and mean comparison (Tukey). It was shown that the application of ultrasound directly to the electrode can significantly improve the efficiency of electrolysis, reducing overvoltage and resistances, and accelerating the formation of hydrogen microbubbles, resulting in up to a 28% increase in hydrogen production. The importance of optimizing parameters such as ultrasonic frequency and intensity and electrolyte concentration is highlighted, offering a promising approach to make green hydrogen production more viable and economical. It is suggested to explore different electrode materials and integrate this technology into renewable energy systems for future research.